Lipid transfer proteins and the tuning of compartmental identity in the Golgi apparatus - McDermott, M.; Mousley, Carl (2016)
The Golgi complex constitutes a central way station of the eukaryotic endomembrane system, an intricate network of organelles engaged in control of membrane trafficking and the processing of various cellular components. Previous ideas of compartmental stability within this network are gradually being reshaped by concepts describing a biochemical continuum of hybrid organelles whose constitution is regulated by compartmental maturation. Membrane lipid composition and lipid signaling processes make fundamental contributions to compartmentalization strategies that are themselves critical for organizing cellular architecture and biochemical activities. Phosphatidylinositol transfer proteins (PITPs) are increasingly recognized as key regulators of membrane trafficking through the secretory pathway. They do so by coordinating lipid metabolism with lipid signaling, translating this information to core protein components of the membrane trafficking machinery. In this capacity, PITPs can be viewed as regulators of an essential lipid-protein interface of cisternal maturation. It is also now becoming appreciated, for the first time, that such an interface plays important roles in larger systems processes that link secretory pathway function with cell proliferation.